Eficácia na redução de recidiva da cirurgia micrográfica versus cirurgia convencional para carcinoma basocelular e carcinoma espinocelular: revisão sistemática e metanálise - Priscila Neri Lacerda [UNESP] (2023)
The standard of care for basal cell carcinoma (BCC) and squamous cell carcinoma (SCC) involves excision by conventional surgery (CS) with a predefined safety margin of resection or micrographic surgery (MS) with microscopic margin control. Previous studies have reported the superiority of MS in reducing recurrences for high-risk BCC and SCC. This systematic review aimed to assess MS and CS recurrence rates by including randomized clinical trials (RCTs) and cohort studies. A systematic review and meta-analysis were conducted for related studies in PubMed, LILACS, EMBASE, SCOPUS, WEB OF SCIENCE, CINHAL, and COCHRANE until May 2023. RCTs and cohorts involving patients with BCC or SCC submitted to MS and CS were included. Risk of bias assessment followed Cochrane-recommended tools for RCTs and cohorts, and certainty of evidence followed the GRADE approach. Pooled estimates were used to determine the relative risk (RR) and absolute risk difference (RD) using a random-effects model. Seventeen studies were included, two RCTs and fifteen cohorts. The combined estimate of RR was 0.48 (95%CI 0.36‒0.63), without heterogeneity nor evidence of publication bias (p>0.3). The RD resulted in 2.9% (95%CI 1.0%‒4.9%; NNT=35). Regarding subgroup analysis, the RR for BBC was 0.37 (95%CI 0.25‒0.54), and RD was 3.7% (95%CI 0.8%‒6.5%; NNT=28). For SCC, RR was 0.57 (95%CI 0.29‒1.13), and RD was 1.9% (95%CI 0.8%‒4.7%; NNT=53). Among primary tumors, RR was 0.39 (95%CI 0.28‒0.54), and for recurrent tumors was 0.67 (95%CI 0.30‒1.50). There is moderate evidence based on two RCTs, and low evidence based on 15 cohort studies that MS is superior to CS in reducing recurrences of BCCs and primary tumors. The development of protocols that maximize the cost-effectiveness of each method in different clinical scenarios is paramount.